2018
DOI: 10.1021/acs.bioconjchem.8b00512
|View full text |Cite
|
Sign up to set email alerts
|

New Lanthanide Chelating Tags for PCS NMR Spectroscopy with Reduction Stable, Rigid Linkers for Fast and Irreversible Conjugation to Proteins

Abstract: Lanthanide chelating tags (LCTs) have been used with great success for determining structures and interactions of proteins and other biological macromolecules. Recently LCTs have also been used for in-cell NMR spectroscopy, but the bottleneck especially for demanding applications like pseudocontact shift (PCS) NMR is the sparse availability of suitable tags that allow for site-selective, rigid, irreversible, fast, and quantitative conjugation of chelated paramagnetic lanthanide ions to proteins via reduction s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 32 publications
(78 reference statements)
2
62
0
Order By: Relevance
“…The tag showed PCS of up to 6.5 ppm when attached to ubiquitin S57 C, and the PCS and tensor anisotropies observed for Ln‐P4M4‐DOTA upon attachment to the protein were significantly increased compared to those of its methylated predecessor (Figures and and ; Table ). The magnitude of the obtained PCS and anisotropy parameters as well as the straightforward application places Ln‐P4M4‐DOTA among the best performing LCTs currently available …”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The tag showed PCS of up to 6.5 ppm when attached to ubiquitin S57 C, and the PCS and tensor anisotropies observed for Ln‐P4M4‐DOTA upon attachment to the protein were significantly increased compared to those of its methylated predecessor (Figures and and ; Table ). The magnitude of the obtained PCS and anisotropy parameters as well as the straightforward application places Ln‐P4M4‐DOTA among the best performing LCTs currently available …”
Section: Resultsmentioning
confidence: 97%
“…The magnitude of the obtained PCS and anisotropy parameters as well as the straightforwardapplication places Ln-P4M4-DOTAamong the best performing LCTscurrently available. [3,9,11,17,19,30,31] The enhanced PCS could be attributedt oo ne or more of the following factors:( i) decreased small-amplitude vibrations of the scaffold,( ii)different positioning of the oxygen donor atomso ft he side arms relative to the nitrogen donors of the basal cyclen,w hich was shown by Mironov et al [32] to significantly affect the observed anisotropies, (iii)alteredm obility or rotationoft he tag on the protein surface. As can be seen from the calculated structure of the Lu-P4M4-DOTAc omplex, the isopropyl groupso nt he backbone lead to extreme overcrowding of the chelating cage ( Figure 10).…”
Section: Properties Of the Isopropyl-substituted Lanthanidechelating mentioning
confidence: 94%
See 2 more Smart Citations
“…The standard strategy is the conjugation by formation of a disulfide bond: this technique has been widely used but it is hampered by the stability of the bond formed . Thus, in recent years, much effort has been concentrated on the design of paramagnetic tags that are stable under reducing conditions once attached to the protein, and which could also be used in cells . For this purpose, copper‐catalyzed azide−alkyne “click” cycloadditions, (which, however, require the introduction of non‐natural amino acids i. e. p‐azido‐phenylalanine in the protein sequence), and thiol‐ene coupling (TEC) (which relies on existing or mutated cysteine residues) have emerged as useful alternative tools in protein chemical conjugation.…”
Section: Introductionmentioning
confidence: 99%